2013
DOI: 10.1371/journal.pone.0053184
|View full text |Cite
|
Sign up to set email alerts
|

Do Children with Uncomplicated Severe Acute Malnutrition Need Antibiotics? A Systematic Review and Meta-Analysis

Abstract: BackgroundCurrent (1999) World Health Organization guidelines recommend giving routine antibiotics (AB) for all children with severe acute malnutrition (SAM), even if they have uncomplicated disease with no clinically obvious infections. We examined the evidence behind this recommendation.Methods and FindingsOVID-MEDLINE, EMBASE, COCHRANE, GLOBAL-HEALTH, CINAHL, POPLINE, AFRICA-WIDE-NiPAD, and LILACS were searched for AB efficacy, bacterial resistance, and infection rates in SAM. Following PRISMA guidelines, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 47 publications
1
74
0
Order By: Relevance
“…Treatment for this condition often involves administration of antibiotics, as recommended by the W orld Health Organization (WHO); however, there is no strong evidence that this is the best course of action. [12] Considering our evidence that even without antibiotic exposure, children at risk of malnutrition often harbour resistance genes, it seems that the introduction of additional selective pressure could actually contribute to ill health rather than recovery. A 2014 study [13] found that the diversity of antibiotic resistance genes in the human gut microbiota appears to increase with age, although they did not look at individuals <3 years of age.…”
Section: Researchmentioning
confidence: 97%
“…Treatment for this condition often involves administration of antibiotics, as recommended by the W orld Health Organization (WHO); however, there is no strong evidence that this is the best course of action. [12] Considering our evidence that even without antibiotic exposure, children at risk of malnutrition often harbour resistance genes, it seems that the introduction of additional selective pressure could actually contribute to ill health rather than recovery. A 2014 study [13] found that the diversity of antibiotic resistance genes in the human gut microbiota appears to increase with age, although they did not look at individuals <3 years of age.…”
Section: Researchmentioning
confidence: 97%
“…[3,4] This may warrant the empiric use of antimicrobials to boost their survival, but in the case of severe acute malnutrition complicated by diarrhea only, this predisposes a child to inappropriate antimicrobial use. [5,6] Antimicrobial resistance among Escherichia coli is of increasing global concern. [7] This has been associated with the emergence and spread of extended spectrum β-lactamase (ESBL)-producing E. coli, which are also frequently associated with resistance to quinolone and aminoglycosides.…”
Section: Introductionmentioning
confidence: 99%
“…Some have focused on comparing the inpatient model with the community model (Lenters et al, 2013;Schooness et al, 2013;Ashworth, 2006); some have assessed the appropriateness and efficacy of routine first-line antibiotics provided during outpatient care for children with uncomplicated SAM (Alcoba et al, 2013); and others have examined the effect of different ready-to-use foods (RUFs), including cost-effectiveness (Bhutta et al, 2008;Gera, 2010). Picot and colleagues (2012) reviewed various intervention studies that have been designed to treat infants and children aged under five years with SAM.…”
Section: Rationale and Purposementioning
confidence: 99%